Conversion of waste tire rubber into a high-capacity adsorbent for the removal of methylene blue, methyl orange, and tetracycline from water. Issue 2 (April 2018) - Islam, Md. Tariqul; Saenz-Arana, Ricardo; Hernandez, Cesar; Guinto, Thomas; Ahsan, Md Ariful; Bragg, Dwayne T.; Wang, Huiyao; Alvarado-Tenorio, Bonifacio; Noveron, Juan C.
Graphical abstract: Conversion of waste tire rubber into a high-capacity adsorbent for the removal of methylene blue, methyl orange, and tetracycline from water. Abstract: There has been growing interest in making adsorbents more cost-effective and feasible in low resource areas by using material that is cheap or would usually be considered waste. In the present study, a high-capacity regenerable adsorbent is synthesized by the treatment of waste tire rubber (WTR) with concentrated sulfuric acid. The sulfuric acid reflux carbonized as well as functionalized the WTR with the sulfonic acid group. The as-prepared sulfonated carbonaceous WTR was used for the removal of organic dyes and antibiotic viz. methylene blue (MB), methyl orange (MO) and Tetracycline (TC) from water. The maximum adsorption capacity was found to be about 833, 588, and 303 mg/g towards MB, MO, and TC, respectively. The adsorption of MB, MO, and TC from the tap water matrix was also performed and shown to maintain similar adsorption capacities as the deionized water. In addition, a packed glass column was prepared to demonstrate the continuous adsorption of MB and TC from the tap water matrix. The regeneration of the column was achieved by using mixture of aqueous and organic solvents with dissolved NaOH and it was demonstrated that the adsorbent not only recovered but also increased its adsorption capacity after every time it was regenerated.